Design Optimization of Heat Exchangers with Advanced Optimization Techniques: A Review - Rao, R. Venkata; Saroj, Ankit; Ocloń, Pawel; Taler, Jan (Archives of computational methods in engineering, 2020)
This literature review presents the extensive literature survey of various heat exchangers (HEs) for the design optimization using advanced optimization techniques concerning with various aspects. The chief objective of this work is to focus on the parametric design optimization of different types of HEs using advanced optimization algorithms and therefore only the research works associated with advanced optimization techniques are considered. This is the first paper which exclusively summaries the research works concerning with the parameter optimization of HEs using advanced optimization techniques. Various types of HEs considered in this review paper are shell-and-tube HEs, plate-fin HEs, fin-tube HEs and various configurations of HE networks etc. The parametric design optimization of HEs is associated with number of structural and physical parameters having highly complexity. Trial and error method is used in the general design approaches and this becomes tediously and time consuming and not having the guarantee of getting an optimum design. Therefore, for the design of HEs advanced optimization techniques are preferred. The review work on parametric design optimization was not attempted previously by taking into consideration various types of HEs therefore this review paper may turn into the complete information at one place and it may be very useful to the industrial design and successive researchers to choose the direction of their research work in the field of parameter optimization of HEs using advanced optimization algorithm.